ULTRASOUND DIAGNOSTIC OF TRAUMATIC RETICULOPERITONITIS IN CATTLE - Solcan, G.; Anton, Alina; Karapinar, T. (General Assoc Romanian Veterinarians, 2018)
Ultrasound is an ideal diagnostic tool for the investigation of bovine gastrointestinal disorders like traumatic reticuloperitonitis, left and right displacement of the abomasum, ileus of the small intestine and dilatation and displacement of the caecum. An ultrasound examination is performed on nonsedated, standing cattle using a 3.5-5 MHz linear or curvilinear transducer after the application of transmission gel. For ultrasound examination of the reticulum, the transducer is applied to the ventral aspect of the thorax on the left and right of the sternum as well as to the left and right lateral thorax up to the level of the elbow. The reticulum is first examined from the left side and then from the right. The normal reticulum appears as a half-moon-shaped structure with an even contour. Traumatic reticuloperitonitis is the most common cause of anterior abdominal pain in cattle. Fibrinopurulent collections may be identified between reticulum and abdominal wall, as hypoechoic collection (purulent liquid, rich in cells) containing irregular hyperechic masses (fibrine).
Keywords: cattle; traumatic reticuloperitonitis; ultrasound examination